22q11.2 Deletion Syndrome in Colombian Patients With Syndromic Cleft Lip and/or Palate. (January 2019) - Carpeta, Suleima; Pineda, Tatiana; Martínez, Maria Claudia; Osorio, Gloria; Porras-Hurtado, Gloria Liliana; Rojas, Jorge; Zarante, Ignacio; Moreno-Niño, Olga María
The objective of this work was to identify 22q11.2 chromosomal deletion in patients with cleft lip and/or cleft palate and suggestive syndromic phenotype in Colombian patients. We studied 49 patients with cleft lip and/or cleft palate, exhibiting additional clinical findings linked to 22q11.2 deletion syndrome. All patients underwent high-resolution G-banded karyotyping, multiplex ligation-dependent probe amplification, and clinical evaluation by a geneticist. Seven patients presented 22q11.2 deletion and 2 patients had other chromosomal abnormalities. In conclusion, this study contributes with new data for genetic etiology in syndromic conditions of oral fissures.